The relationship between FDI, political and institutional risk in Sub-Saharan Africa - Matima, Zorodzai (Graduate School of Business (GSB), 2022)
This study uses Generalised Meod of Moments to investigate the roles of political risk and institutional quality determinants of Foreign Direct Investment inflows to 20 countries in SubSaharan Africa between 2003 and 2019. The results show that both political risk and weak institutional quality significantly and negatively affect FDI in Sub-Saharan Africa. The GMM interaction terms for institutional quality are larger than those for political risk. These results emphasize the importance of institutional quality above that of the political system, suggesting that institutional quality is more attractive to foreign investors than a sound political system. This is probably because foreign investors are more concerned with long-run regulatory enforcement and investment protection than by short-run political dynamics.